Can civil society reclaim truth?: Results from a community-based truth and reconciliation commission - Androff, David K. (International journal of transitional justice, 2012)
The Greensboro Truth and Reconciliation Commission (GTRC) was a grassroots initiative with no state sanction, organized and supported solely by civil society. Its purpose was to discover and disseminate the truth about a racially motivated shooting by members of the Ku Klux Klan in 1979. This article asks whether such an initiative can succeed in seeking the truth in the same way that a formal transitional justice measure would. It reviews how the GTRC originated from civil society, how it was funded and its truth-seeking mandate, and presents data from qualitative interviews with victims of the shooting who participated in the GTRC. The article demonstrates how the GTRC faced significant obstacles to truth seeking, including lack of participation from many perpetrators, local government and law enforcement and lack of engagement from a wider segment of Greensboro. Nonetheless, the GTRC stands as an example of participatory democracy and of how civil society can accomplish truth seeking despite government resistance.